An iterative method to infer distributed mass and stiffness profiles for use in reference dynamic beam-Winkler models of foundation piles from frequency response functions - Wu, W.H.; Prendergast, L.J.; Gavin, K. (Elsevier, 2018)
Accurate characterisation of soil behaviour in Dynamic-Soil-Structure Interaction (DSSI) applications remains a significant challenge. Knowledge of the operational soil-structure interaction stiffness is important for applications ranging from earthquake engineering to offshore structures subjected to wind and wave loading. A number of methods have been derived to couple soil and structural properties using beam-Winkler models. One of the key drawbacks of these approaches is the disparity in predicted stiffness depending on the formulation chosen. Moreover, the contribution of soil mass in the dynamic motion of foundations is often neglected. In this paper, a method is presented that uses a Frequency Response Function (FRF) measured from a laterally-impacted pile to estimate operational stiffness and mass profiles acting along the pile. The method involves creating a beam-Winkler numerical model of the soil-pile system, applying a starting estimate of the soil stiffness and mass profiles and calculating weighting factors to be applied to these starting estimates to obtain a match between the measured FRF from the test pile and the calculated FRF from the numerical model. This paper presents the formulation of the iterative updating approach, and demonstrates its functionality using simulated experimental data of typical piles. Simulated data is used as it enables testing a wide range of circumstances including possible issues relating to the influence of the shape of the operational soil stiffness profile, soil density, effects of sensor noise and errors in damping estimation. The method may be useful in finite-element (FE) model updating applications where reference numerical models for soil-structure interaction are required.